Evaluación antropométrica de los colectivos ciclistas de la ciudad de Loja. - Sigcho Cueva, José Carlos (2015)
The increase increment in the use of bicycles in Loja city and the lack of evaluation of the physical condition of cyclists, can determine is determining health risks. To solve tackle this problem, it was proposed, rate the collection of anthropometric measurements of the members of ciclists groups of cyclists in Loja was proposed. This collection took place, during the period from of April to July 2014, in order to implement preventive measures in health care. The study was descriptive., It involveding 75 cyclists (61 men and 14 women), mean with an avarage age of 29, a range between 16 and -65 years-old., in whom a structured survey, and afterwards the following was applied and measures were taken: as weight, height, skinfold thickness (triceps , sudescapular, suprailiac, adbominal, quadriceps and calf). By using the formulas of Mosteller and Du Bois & Du Bois body surface area was obtained.; and by using the formula of Yuahsz, ’s formula for men, and the formula of Carter,’s for women, fat percentage was obtained. The results, were obtained from 10 groups of cyclists groups in Loja city, showed that; the most common modality corresponds to cross-country (24%), followed by cycling tourism (12%). and other modalities such as: road, down-hill, urban cycling, BMX have a lower percentage of participants.do in smaller percentage; the percentage of body fat found was: low 16%, normal 72%, limit 9.30% and 2.7% obesity., important to mention that all women haved low body fat percentage.; and, the method practisced by the cyclist does not seem to directly correspond with their physical condition.; In conclusion, based on this anthropometric assessment Loja’s there are indeed cyclists present health risks for cyclists in the city. Keywords: anthropometry, cyclists, fat percentage, body surface area.